Study on Mechanical Properties of Cement–Jute Fiber Modified Weak Expansive Soil - Xuelei Cheng; Qiqi Li; Ran Hai; Shunqun Li; Cun Hui; Zhizeng Zhang (Advances in Civil Engineering)
Sixteen groups of comprehensive tests were undertaken to examine the modifications in the mechanical characteristics of weak expansive soil resulting from the inclusion of a composite material comprising cement and jute fibers. The aim of the tests was to analyze the unconfined compressive strength and shear strength. The results reveal that (1) as the modified material content increased, the stress–strain curve of the modified soil progressively became steeper, with a more pronounced peak value. Under the same strain condition, the stress variation increased accordingly. After the stress reached its maximum, a sudden phenomenon of brittle axial compression failure occurred. (2) With the increase in cement content, the unconfined compressive strength and shear strength of the modified expansive soil gradually increased, reaching the highest shear strength when the cement content was 8%. With the increase in jute fiber content, the unconfined compressive strength and shear strength of modified expansive soil increased first and then decreased, reaching the highest value when the content was 0.5%. (3) The cohesion of modified expansive soil increased with the increase in cement content. When the cement content was 8%, the cohesion of the soil sample was as high as 298.29 kPa. The cohesion of modified expansive soil increased first and then decreased with the increase in fiber content. When the jute fiber content was 0.5%, the cohesion reached the maximum value. (4) The internal friction angle of the modified expansive soil increased with the increase in cement content. When the cement content was 8%, the internal friction angle of the soil sample increased by 2.64°. The cohesion of modified expansive soil increased first and then decreased with the increase in fiber content. When the jute fiber content was 0.5%, the internal friction angle reached the maximum value.